ANALISIS PENGARUH KUALITAS PELAYANAN KONSUMEN PADA WARUNG UCOK DURIAN ISKANDAR MUDA MEDAN TERHADAP KEPUTUSAN PEMBELIAN - thomson parlindungan siburian; liasta ginting (Universitas Sumatera Utara, 2013)
Abstrak This study aims to determine and analyze the influence of service quality Ucok Durian at Iskandar Muda Medan on the purchase decisions. The hypothesis of this study is the factor of service quality that includes variable tangibles, reliability, responsiveness, assurance, and emphaty has positive and significant impact on purchasing decisions towards Warung Ucok Durian at Iskandar Muda Medan. The sampling using the technique of Purposive Sampling. Data analysis methods used is descriptive and multiple linear regression. The results of this study indicate that based on the F test, the service qualities consisting of tangibles variable, reliability, responsiveness, assurance, and emphaty simultaneously have a positive and significant impact on purchasing decisions towards Warung Ucok Durian at Iskandar Muda Medan. Based on the results of the t test, variable influence positive and significant on purchasing decisions is the variable of reliability and responsiveness. Adjusted R Square value = 0.152 means that 15.2% of the purchase decision factors can be explained by the independent variables (physical evidence, reliability, responsiveness, assurance, and emphaty) while the remaining 84.8% is explained by other factors which is not examined in this study. Keywords: Tangibles, Reliability, Responsiveness, Assurance, and Emphaty and Purchasing Decisions.